SIFAT VENIR DAN KAYU LAPIS 8 JENIS KAYU DARI SULAWESI TENGAH - M I Jslrandar; Suwandi Kliwon; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
A muly reault on• the suitability of 8 wood 1peciesfrom Central Sulawesia raw material-for veneeri and plywood iB re rted in hiB paper. 1'ae •tudy cons!ited of log peeling characteristic, veneerpropgty 'and tome phy cal/mechanical AU of ita. lo,. Tram wood speciu could be peeled in cold c0ndition, producing 0.9 mm and 1.6 mm veneer at propertitia of plywood (tripl• and multiplaa cuffln6 angle between 910 - 92080'. • - .7'le average111rinkage of veneer iB 6.27%, with a minimum of 4.98'fo (Nyatoh) and maximum of 8.14% (Palapi). Veneer •welling from oven_-dry to aiNlry condition varied between 2.lB'fo (Nyatoh) and 8.60% (Durian) with an avera.e- 2.81'-'. '7'1, bondi!JI atrerwth of _p_'f¥_ fro_ - woo4_•!!1!'*-• (76_'fo) ti>ntOrms with the Indonaian ttandard for type IIor